PENGEMBANGAN MEDIA INTERAKTIF “MAKPEN” (MAKNA DAN PENERAPAN) MATERI SILA PANCASILA UNTUK SISWA SEKOLAH DASAR - Rosita Eka Saputri; Ilmawati Fahmi Imron; Aan Nurfahrudianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the limited use of instructional media in the teaching and learning process at elementary schools, particularly in the subject of Pancasila Education, focusing on the material about the principles (sila) of Pancasila. Learning is still heavily dependent on textbooks, worksheets, and other printed sources, making it difficult for students to understand the meaning and application of each Pancasila principle. Schools also have not fully optimized the use of facilities such as Chromebooks and projectors. In Grade IV, the material discusses the meaning and examples of applying Pancasila principles in daily life. The use of media is very helpful in the learning process. The researcher developed an interactive learning media called “Makpen” to assist both teachers and students, specifically for learning the Pancasila principles. The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The aim of this study is to determine the validity and practicality of the “Makpen” interactive learning media. The results showed: (1) media expert and material expert validation scores were 92% respectively; and (2) teacher responses reached 96%, student responses in the limited trial were 94%, and in the wider trial were 96,4%. Based on these results, the “Makpen” interactive learning media is considered very valid, practical, and feasible to use in the learning process. The “Makpen” media is valid, practical, and effective for learning the meaning and application of Pancasila principles. Theoretically, this media enhances students’ understanding. Practically, it can serve as a reference for teachers and increase students’ learning motivation. The researcher suggests the development of other technology-based instructional media to make learning more engaging and meaningful.